Breaking Seed Dormancy in Tamarind (Tamarindus Indica) A Case Study of Gombe Local Government Area - ZA Abubakar; A Muhammad (Journal of Applied Sciences and Environmental Management)
The study was carried out to investigate the effects of sulphuric acid and hot water treatments on the germination of Tamarind (Tamarindus indica). Seeds were sown in poly pots under normal environmental condition for germination. Thirty (30) seeds of T. indica (one seed per pot) with ten replicates each were used. The highest germination percentage was recorded in seeds treated with fifty (50%) percent sulphuric acid concentration within sixty (60) minutes soaking period. Germination was observed to be enhanced by the effect of sulphuric acid on disrupting the seed coats of Tamarind (Jabbe), followed by hot water. Results of this research may serve as useful information in the production and improvement of the tree species, as knowledge on seed germination requirements is a critical factor in seedlings production